ASSESSING THE PERFORMANCE OF STATE-OWNED ENTERPRISES IN MONTENEGRO - Vujošević, Nina (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
The average stock of state-owned enterprises (SOEs) assets in Montenegro accounts for almost 100 percent of the GDP. SOEs in Montenegro are concentrated in natural monopoly sectors such as energy, transportation, water supply, waste management, and tourism. A SOEs employment footprint in Montenegro accounts for almost 10 percent of total employment which is rather high and similar to some other South-East Europe developing economies. The objective of this research is to analyze fiscal risks stemming from the 20 largest out of 45 central-government-owned SOEs and to show whether SOEs’ corporate governance weaknesses are at the root of the arising fiscal risks. The methodology used in the research, first includes the OECD corporate governance criteria implementation to measure the stance of corporate governance of 20 analyzed SOEs. The second step of the research methodology is about carrying out a financial ratio analysis to identify fiscal risks stemming from SOEs and confirm whether the fiscal risks are increasing if SOEs’ corporate governance is weak. Assessing fiscal risks for the selected group of SOEs is based on the IMF methodology that defines a threshold to assess whether the financial performance of SOEs leads to fiscal risks. Although having a prominent role in the Montenegrin economy, weaknesses in SOEs’ corporate governance reflected in inefficiencies in their management impose substantial financial and fiscal costs. Looking a few years backward, the economic performance of SOEs varies across sectors from profitable SOEs in the energy sector to loss-making enterprises in transportation.
Keywords: corporate governance, a state-owned enterprise, oversight, fiscal risks